Tissue plasminogen activator, plasminogen activator inhibitors, and activator-inhibitor complex in liver disease. Issue 3 (March 1994) - Leiper, K; Croll, A; Booth, N A; Moore, N R; Sinclair, T; Bennett, B
Abstract : AIMS--To identify the relative contribution of plasminogen activators, particularly tissue plasminogen activator (t-PA) and specific plasminogen activator inhibitors (PAI-1, PAI-2), to the fibrinolytic changes associated with various types of liver disease or severe chemical and physical damage to the liver. METHODS--Platelet rich (PRP) and platelet poor plasma (PFP) from patients with alcoholic cirrhosis, primary biliary cirrhosis, hepatic malignancy, or paracetamol overdose, or who were undergoing partial hepatectomy or liver transplantation, were assayed for t-PA, PAI-1, t-PA-PAI-1 complex and PAI-2 antigen values using specific enzyme linked immunosorbent assays (ELISAs) developed in this laboratory. RESULTS--Appreciable increases in the plasma concentration of t-PA, PAI-1, and t-PA-PAI-1 were seen in patients with alcoholic cirrhosis, primary biliary cirrhosis, and hepatic malignancy. Liver damage due to paracetamol overdose and partial hepatectomy both resulted in a striking increase in plasma PAI-1 concentration, although concentrations of t-PA and t-PA-PAI-1 complex were less affected. Concentrations of t-PA, PAI-1, and t-PA-PAI-1 complex returned to near normal values after successful liver transplantation in a patient with chronic active hepatitis. PAI-2 was also detected in several patients with chronic liver disorders. CONCLUSIONS--Haemorrhage due to fibrinolytic bleeding is commonly associated with liver disease. The patients studied here all had appreciable increases in circulating t-PA antigen concentrations. This was associated with increased concentrations of PAI-1 antigen and t-PA-PAI-1 complex and the balance between activator and inhibitor did not result in systemic plasmin generation. Reduced PAI-1 activity in cirrhosis or a critical difference in the ratio of t-PA to PAI-1 concentrations may explain the enhanced plasminogen activator activity previously noted in cirrhosis but not metastatic disease. Reduced hepatic clearance of t-PA and t-PA-PAI-1 complex due to impaired liver function may account for increased concentrations of free and complexed t-PA.